Homage to Hersteinsson and Macdonald: climate warming and resource subsidies cause red fox range expansion and Arctic fox decline - Elmhagen, Bodil; Berteaux, Dominique; Burgess, Robert M.; Ehrich, Dorothee; Gallant, Daniel; Henttonen, Heikki; Ims, Rolf A.; Killengreen, Siw T.; Niemimaa, Jukka; Norén, Karin; Ollila, Tuomo; Rodnikova, Anna; et al. (Polar research, 2017)
Climate change can have a marked effect on the distribution and abundance of some species, as well as their interspecific interactions. In 1992, before ecological effects of anthropogenic climate change had developed into a topical research field, Hersteinsson and Macdonald published a seminal paper hypothesizing that the northern distribution limit of the red fox (Vulpes vulpes) is determined by food availability and ultimately climate, while the southern distribution limit of the Arctic fox (Vulpes lagopus) is determined by interspecific competition with the larger red fox. This hypothesis has inspired extensive research in several parts of the circumpolar distribution range of the Arctic fox. Over the past 25 years, it was shown that red foxes can exclude Arctic foxes from dens, space and food resources, and that red foxes kill and sometimes consume Arctic foxes. When the red fox increases to ecologically effective densities, it can cause Arctic fox decline, extirpation and range contraction, while conservation actions involving red fox culling can lead to Arctic fox recovery. Red fox advance in productive tundra, concurrent with Arctic fox retreat from this habitat, support the original hypothesis that climate warming will alter the geographical ranges of the species. However, recent studies show that anthropogenic subsidies also drive red fox advance, allowing red fox establishment north of its climate-imposed distribution limit. We conclude that synergies between anthropogenic subsidies and climate warming will speed up Arctic ecosystem change, allowing mobile species to establish and thrive in human-provided refugia, with potential spill-over effects in surrounding ecosystems.